'Children, families and the conundrum about men': Exploring factors contributing to father absence in South Africa and its implications for social and care policies. Issue 2 (2nd April 2016) - Patel, Leila; Mavungu, Eddy Mazembo
ABSTRACT: South Africa has an exceptionally high number of absent fathers. Approximately half of the children in the county are living without daily contact with their fathers, which is assumed to have dire social and economic consequences for them, their families and communities. Despite growing societal interest in the phenomenon of absent fathers, social and family policies are silent about the role of men or fathers in a highly feminised, familial and community centred welfare and care regime. This article explores factors that contribute to father absence from their own standpoint. It draws on focus group discussions with absent fathers in four urban communities in Johannesburg, South Africa. Factors, such as materialist constructions of fatherhood and masculinity, as well as socio-economic, cultural and relational factors, provide some insight into the phenomenon. Although the findings were exploratory, they nevertheless raise important questions about reforming care policies in both the private and public spheres to meet the dual challenges of care and gender equality in a Southern context.